Antibacterial Weapons: Targeted Destruction in the Microbiota. Issue 4 (April 2018) - Chassaing, Benoit; Cascales, Eric
Abstract : The intestinal microbiota plays an important role in health, particularly in promoting intestinal metabolic capacity and in maturing the immune system. The intestinal microbiota also mediates colonization resistance against pathogenic bacteria, hence protecting the host from infections. In addition, some bacterial pathogens deliver toxins that target phylogenetically related or distinct bacterial species in order to outcompete and establish within the microbiota. The most widely distributed weapons include bacteriocins, as well as contact-dependent growth inhibition and type VI secretion systems. In this review, we discuss important advances about the impact of such antibacterial systems on shaping the intestinal microbiota. Highlights: The intestinal microbiota is a complex but stable ecosystem that plays a central role in human health, and disturbance of its composition and function is associated with many diseases. Within the intestinal microbiota, bacteria exchange material and information. The microbiota can be peaceful, but many bacteria fight with others to have a better access to their niche or nutrients. Different antibacterial weapons have been identified and characterized, and many bacterial pathogens use these weapons to establish themselves in the intestinal environment, whereas some commensals use these weapons to specifically target pathogens, leading to protection of the host.